The Impact of Electronic Word of Mouth, Destination Image, and Tourism Attractions on Tourists’ Visit Decisions in Kulon Progo - Yuliantoro Toro; Agus Tri Basuki; Ahmad Ma'ruf (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
Tourism development plays a strategic role in supporting regional economic growth by increasing local revenue, creating employment opportunities, and improving community welfare. In the digital era, tourists increasingly rely on online information and destination perceptions when making travel decisions. This study aims to analyze the influence of Electronic Word of Mouth (EWOM), destination image, and tourist attraction on tourists’ visiting decisions at tourism destinations in Kulon Progo Regency. This research employed a quantitative approach using primary data collected through questionnaires distributed to tourists. The data were analyzed using multiple linear regression analysis to examine the effect of each independent variable on visiting decisions. The results indicate that EWOM, destination image, and tourist attraction have a positive and significant effect on tourists’ visiting decisions, both partially and simultaneously. Destination image is identified as the most dominant variable influencing visiting decisions, followed by EWOM and tourist attraction. Furthermore, the simultaneous test shows that the three variables significantly influence visiting decisions with an Adjusted R Square value of 0.908, indicating that 90.8% of the variation in visiting decisions can be explained by the proposed model. These findings highlight the importance of digital communication, positive destination perception, and attractive tourism resources in influencing tourists’ travel decisions.